Applying Sharia Economic Law Principles to Round The Price of Digital Scales (A Case Study of Buying and Selling in the Prambanan Market, Sleman Regency) - Hasanah, Uswatun; Hambali, Ahmad Imam (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
The Prambanan Market is a traditional market managed by the Sleman Regency Government's Technical Service Unit (UPT) Group VI Market Services. It is located on Jalan Raya Piyungan, a major highway between Solo-Yogyakarta in Bokoharjo village, Prambanan District, Sleman Regency, Yogyakarta Special Region Province. Prambanan market traders are accustomed to using digital weighing devices located on the third floor, which serve as wholesale vegetable centres. Traders often round prices using digital scales, claiming that doing so makes calculations and refunds easier. This study is a descriptive qualitative study based on field research that utilized data collection methods such as observation, interviews, and documentation. The study revealed that certain traders in the Prambanan market engage in price rounding for the sake of convenience in calculation and refunds. Buyers, including customers, are familiar with this method. New buyers may negotiate until they decide to purchase goods at a fair price. From an Islamic law perspective, this method does not fulfil the principles of balance, benefit, or justice in mu'āmalah transactions. This is because sellers use coercion and manipulation to increase their profits.